Observation on responsive OCV variation od Zinc-Air cell with relative humidity content - Manshor, Hanisah; Othman, Raihan; Nordin, Anis Nurashikin; Ani, Mohd Hanafi; Saputra, Hens (IIUM Press, 2011)
Zinc/MCM-41/air cell, in its dry form without the electrolyte, demonstrates humidity sensing property. A good linear correlation between the cell’s open circuit voltage (OCV) and the relative humidity content is observed. The system possesses the potential to be developed into a low cost microhumidity sensor. An ultra thin cell of thickness not more than 40 μm has been fabricated and its use as a humidity sensor is substantiated.